2018
DOI: 10.1007/s12197-018-9427-0
|View full text |Cite
|
Sign up to set email alerts
|

Oil speculation and herding behavior in emerging stock markets

Abstract: This paper explores the relationship between stock and commodity markets from a novel perspective by examining the relationship between speculation in the oil market and investor herding in stock markets. Using firm level data from three energy importing and exporting nations, namely Russia, Brazil, and Turkey, we show that these markets often switch between herding and anti-herding states, while herding is more prevalent in the case of Russia. We also find that speculative activities in the global oil market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
(41 reference statements)
2
20
0
Order By: Relevance
“…Studies investigating herding phenomena have made their appearance earlier and this issue has attracted more attention lately. Pindyck and Rotemberg (1990) , Cakan et al. (2019) , and Júnior et al.…”
Section: Studies About Herding Phenomena In Traditional Financial Assmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating herding phenomena have made their appearance earlier and this issue has attracted more attention lately. Pindyck and Rotemberg (1990) , Cakan et al. (2019) , and Júnior et al.…”
Section: Studies About Herding Phenomena In Traditional Financial Assmentioning
confidence: 99%
“…Studies investigating herding phenomena have made their appearance earlier and this issue has attracted more attention lately. Pindyck and Rotemberg (1990), Cakan et al (2019), andJúnior et al (2019) constitute academic papers that look into this nexus. One of the initial papers has been Pindyck and Rotemberg (1990) that identify co-movements among the prices of raw commodities and argue that these commodities are seemingly unrelated.…”
Section: Herding Phenomena In Commodity Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the value relevance of accounting information is significantly lower in periods defining herding behavior. The latest study by Cakan et al (2019) tested herding in the oil and stock markets among emerging Investors herding in emerging economies economies of Russia, Brazil and Turkey from 2005 to 2015 reported evidence of herding in all three economies; moreover, Russia and Brazil are more prevalent in herding behavior. A recent study on the relationship between herding and liquidity in the Vietnamese stock market by Vo and Phan (2019) showed that herding is more pronounced under high and medium liquidity conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, only a few studies focus on the oil market as a driver of herding behavior in such markets. More specifically, a significant effect of oil price on herding is found in the GCC stock markets (Balcilar et al , 2013, 2014; Ulussever and Demirer, 2017), American industries (Ben Mabrouk and Litimi, 2018), Moscow Exchange (Indārs et al , 2019) and Russia, Brazil, and Turkey (Cakan et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%